A low power and energy efficient 4:2 precise compressor based on novel 14T hybrid full adders in 10 nm wrap gate CNTFET technology. (October 2020) - Jooq, Mohammad Khaleqi Qaleh; Bozorgmehr, Ali; Mirzakuchaki, Sattar
Abstract: In the realm of VLSI circuits, addition and multiplication are the most pivotal operators in arithmetic units. In this regard, this work aims to propose an energy efficient 4:2 precise compressor utilizing 10 nm wrap gate CNTFET technology. The proposed compressor is constructed from 2 hybrids 14-transistors full adders. The proposed Gate All Around (GAA) CNTFET based full adder employs a hybrid XOR/XNOR logic structure to lower the transistor count and power consumption. After performing rigorous simulations, we have demonstrated that the proposed GAA CNTFET based full adder and 4:2 compressor depict 175.3 nW and 308.5 nW power consumption respectively along with superior propagation delay response (4.4 ps and 10.57 ps respectively) at a 0.5 V nominal supply voltage. Moreover, the proposed designs occupy a lower layout area (0.195 μm 2 and 0.43 μm 2 for the proposed full adder and 4:2 compressor respectively) compared to the other counterparts. Our results accentuate the application of the proposed GAA CNTFET based 4:2 precise compressor for ultra miniature microprocessing systems. Highlights: An energy efficient 4:2 precise compressor has been proposed based on 10 nm GAA CNTFET technology. By utilizing ultra-compact 14T full adders, the proposed 4:2 precise compressor has only 28 transistors. To reduce the transistor count in the proposed full adder, a hybrid XNOR/XOR gate with employing only 6 transistors has been demonstrated. The main benefit of the proposed full adder and precise 4:2 compressor is the full-swing operation and elimination of unknown logic states at the outputs. With a 0.5 V nominal power supply, the proposed full adder and 4:2 compressor consume 175.3 nW and 308.5 nW power with 4.4ps and 10.75ps delay response respectively.